Створення бази комплементарних гнутозварних профілів решітчастих металоконструкцій - Портнов, Г. Д.; Тихий, А. А.; Дарієнко, В. В.; Пукалов, В. В.; Кузик, О. В.; Гасенко, Л. В.; Portnov, G.; Tykhyi, A.; Dariіenko, V.; Pukalov, V.; Kuzyk, O.; Hasenko, L. (ЦНТУ, 2024)
Дослідження присвячено розробці бази даних комплементарних гнутозварних профілів для автоматизованого проектування решітчастих металоконструкцій. Значна увага приділяється урахуванню місцевої стійкості та технологічних обмежень сполучення елементів металевих конструкцій ферм. Описано методику аналізу моделей проміжних вузлів з прямокутних труб у програмі SolidWorks і обробку результатів у Microsoft Excel, що дозволяє групувати елементи в комплементарні поєднання профілів. Результати дослідження демонструють зв'язок технологічних обмежень з міцністю елементів та спрощують процес підбору профілів за ДСТУ EN 10219-2:2009, мінімізуючи недонапруження до 5%. This article discusses the development of a database for complementary bent-welded profiles, which facilitates the automation of the design of lattice metal structures. The main focus is on determining the conditions necessary to create efficient and technologically optimized solutions for metal trusses, taking into account the local stability of elements and the limitations of technological connections. The methodology involves analyzing models of rectangular tube intermediate assemblies in Solid Works and processing the results in Microsoft Excel, which allows elements to be grouped into complementary profile combinations. This study helps to link technical constraints to the strength of elements and simplifies the selection of profiles in accordance with DSTU EN 10219-2:2019, minimizing under loading by up to 5%.
Creating a database of complementary bent-welded profiles of lattice metal structures
Keywords: металеві конструкції; сталева ферма; трикутна решітка; гнутозварні профілі; metal structures; steel truss; triangular lattice; bent-welded profiles